Reconstructing identities in higher education : the rise of "third space" professionals - Whitchurch, Celia (New York, NY : Routledge, 2013)
'Intellectual leadership in Higher Education draws on studies conducted in Australia, the United Kingdom and the United States, this book focuses on the growing number of staff who undertake roles associated with broadly based projects that are emerging in higher education institutions. These include aspects such as student life and welfare, widening participation, learning support, community partnership, research and business partnership, and institutional research. Some academic staff are moving in a increasingy project-oriented direction, effectively creating a Third Space between professional and academic spheres of activity. Associated with these changes, the concept of service has become re-oriented towards one of partnership between professional and academic colleagues, students and external agencies. Lateral networks are becoming more significant than traditional linear relationships, and individuals may identify more closely with projects and teams than with formal organisational structures. The concept of Third Space is offered as a way of exploring the emergence of less boundaried roles and identities in higher education community, and of considering the implications of these for individuals and institutions. This book explores the significance of relationships as a key variable in Third Space environments and looks into the development and use of appropriate forms of language to facilitate communication between a range of constituencies. Importantly, it recognises the paradoxes and dilemmas that are likely to arise in Third Space, and how these might be used in positive ways. The book is split into three sections which look at: Literary understandings about professional and academic identities and an introduction to the concept of Third Space. The characteristics of Third Space professionals, including the knowledges, relationships, legitimacies and languages that they create. The implications for individuals and institutions of the developments described, and their possible futures in management and leadership. Intellectual leadership in Higher Education will be of great interest to professional and academic staff who find themselves working in Third Space environments; to those to whom such staff may be responsible, including senior management teams; and also to academic researchers interested in changing identities in higher education'--
'Drawing on studies conducted in Australia, the United Kingdom and the United States, this book focuses on a growing number of staff who undertake roles associated with broadly based projects that have emerged in higher education institutions, including student life and welfare, widening participation, learning support, community partnership, research and business partnership, and institutional research. At the same time as professional staff are acquiring academic credentials, some academic staff are moving in a more project-oriented direction, effectively creating a Third Space between professional and academic spheres of activity. Associated with these changes, the concept of service has become re-oriented towards one of partnership between professional and academic colleagues, students and external agencies. Furthermore, although hierarchical line relationships continue to exist, these may be less significant in day-to-day working than lateral networks, and individuals may identify more closely with projects and teams than with formal organisational structures. Yet such developments have tended to occur'under the radar', and have not been fully articulated. The concept of Third Space is offered as a way of exploring the emergence of less boundaried roles and identities in higher education community, and of considering the implications of these for individuals and institution'--
Includes bibliographical references (p. [151]-162) and index.
Keywords: College teachers -- Professional relationships -- Cross-cultural studies; Universities and colleges -- Professional staff -- Employment -- Cross-cultural studies; Group identity -- Cross-cultural studies